Information technology adoption in small and medium-sized enterprises; an appraisal of two decades literature - Ghobakhloo, Morteza; Sabouri, Mohammad Sadegh; Tang, Sai Hong; Zulkifli, Norzima (World Centre for Academic Research, 2011)
Small to medium-sized enterprises (SMEs) account for major source of employment, technological advancements, and competitive advantages for both developed and developing countries. Owing to the intensified competitive pressure and necessity for entering to global market undergone by SMEs, these businesses are incrementally employing Information Technology (IT) to take advantage of its substantial benefits. Most of prior researches have more focused on IT adoption in large organizations. However, and with regard to the limited resources controlled by SMEs, the process of IT adoption in this business sector is considerably different. The purpose of this paper is to analyze and contrast the internal and external issues affecting the process of IT adoption in SMEs to provide clearer understanding of this process by reviewing IT adoption literature, which includes more than 20 years of empirical research and case studies from a variety of databases with high concentration on certain SME-related issues. Proposed integrated framework demonstrates the process of IT adoption in SMEs through reviewing exiting perspectives in the literature. This study will assist different parties involved with adoption process including managers, vendors, consultants, and governments to achieve a practical synopsis of the IT adoption process in SMEs, which is believed to assist them with successful adoption.